Experimental Study on the Effect of Boric Acid Corrosion on the Performance of Reinforced Concrete. (19th June 2021) - Wang, Qianying; Zhang, Jigang; Shan, Mingchao; Yu, Bingying; Zhao, Yang; Yang, Ran
Abstract : In this study, the effect of boric acid in the cooling water system of nuclear power plants on the durability of reinforced concrete was experimentally studied. The mechanical properties of reinforced concrete under boric acid solution environments were studied by accelerated test methods. In addition, the effect of boric acid on the electrochemical behavior of steel bar and microstructure of concrete was studied. The results showed that boric acid corrosion does not affect reinforced concrete to a large extent, as corrosion only occurs on the surface of reinforced concrete, and thus, the internal reinforced concrete still maintains a high alkaline environment. At a boric acid concentration of 3%, corrosion products are crystallized on the surface of the specimen, which inhibits further corrosion.